Social Media Usage, Overload and Exhaustion: A Performance Perspective - Kamal, Nida; Rabbani, Sajeela; Samdani, Hina; Shujaat, Sobia; Ahmad, Mubashir (International Review of Management and Marketing, 2020)
This study is focused on investigating the negative consequences of social media usage at work through overloads that are a cause of exhaustion and ultimately impact performance. Performance of employee is taken as criterion of exhaustion. Three categories of overloads social overload, communication overload and information overloads serve as mechanism of negative consequences of social media during working hours. A sample of 300 employees of telecom sector of Pakistan contributed in the study. Data was analyzed by using partial least squares structural equation modelling (PLS-SEM) technique. Results revealed that excessive use of social media positively influence information, communication and social overload. Information and communication overload were also found to have an enhanced effect on exhaustion of social media while social overload could not. Performance of employee was also found to be negatively influenced by exhaustion of social media. Study limitations and future directions are also discussed. Keywords: Performance; Social Media; Exhaustion; Telecom Sector JEL Classification: D89 DOI: https://doi.org/10.32479/irmm.10190